Electronic textile electrocardiogram monitoring in cardiac patients: a scoping review protocol. (February 2019) - Teferra, Meseret N.; Kourbelis, Constance; Newman, Peter; Ramos, Joyce S.; Hobbs, David; Clark, Robyn A.; Reynolds, Karen J.
Abstract : Review question/objective: This scoping review aims to explore and scope the literature and research on the use of e-textile electrocardiogram (ECG) monitoring in cardiac patients and provide a unique contribution to the available evidence. The objectives of this scoping review are: To explore, organize and present the existing research literature on the use of e-textile based (resting, signal-averaged, ambulatory or exercise) ECG monitoring in cardiac patients. To assess the gaps in the application of e-textile technologies for (resting, signal-averaged, ambulatory or exercise) ECG cardiac monitoring. The questions of this review are: What is known from the existing literature about utilizing e-textile ECG to monitor cardiac patients? What are the basic physiological parameters monitored using e-textile based ECG monitoring of cardiac patients? Considering e-textile based ECG monitoring of cardiac patients: How many and what type of sensors are required for precise detection of the respective parameters? How are the issues of data storage, connectivity and power requirements addressed? How are signal quality and stability managed for extended ambulatory activities?